Effect of circumferential resection margin status on survival and recurrence in esophageal squamous cell carcinoma with neoadjuvant chemoradiotherapy - Gu, Yi-Min; Yang, Yu-Shang; Kong, Wei-Li; Shang, Qi-Xin; Zhang, Han-Lu; Wang, Wen-Ping; Yuan, Yong; Che, Guo-Wei; Chen, Long-Qi (Frontiers in Oncology, 2022)
Background The aim of this study was to investigate whether circumferential resection margin (CRM) status has an impact on survival and recurrence in esophageal squamous cell carcinoma after neoadjuvant chemoradiotherapy. Methods We screened patients with esophageal squamous cell carcinoma who underwent esophagectomy from January 2017 to December 2019. The CRM was reassessed. Patients were grouped into a CRM of 1 mm or less (0 < CRM ≤ 1 mm) and a CRM greater than 1 mm (CRM>1 mm). The impact of CRM on survival was investigated using Kaplan–Meier analysis and Cox regression modeling. The optimal CRM cut point was evaluated using restricted cubic spline curve. Results A total of 89 patients were enrolled in this study. The CRM status was an independent risk factor for the prognosis (HR: 0.35, 95% CI: 0.16-0.73). Compared with a CRM of 1 mm or less, a CRM greater than 1 mm had better overall survival (HR: 0.35, 95% CI: 0.16-0.73, log-rank P = 0.011), longer disease-free survival (HR: 0.51, 95% CI: 0.27-0.95, log-rank P = 0.040), and less recurrence (HR: 0.44, 95% CI: 0.23-0.85, log–rank P = 0.015). We visualized the association between CRM and the hazard ratio of survival and identified the optimal cut point at 1 mm. Conclusions A CRM greater than 1 mm had better survival and less recurrence compared to a CRM of 1 mm or less. A more radical resection with adequate CRM could benefit survival in patients with esophageal squamous cell carcinoma after neoadjuvant therapy.